Estimating Hispanic-white wage gaps among women: The importance of controlling for cost of living - Peter McHenry; Melissa McInerney (W.E. Upjohn Institute for Employment Research, 2015)
Despite concern regarding labor market discrimination against Hispanics, previously published estimates show that Hispanic women earn higher hourly wages than white women with similar observable characteristics. This estimated wage premium is likely biased upwards because of the omission of an important control variable: cost of living. We show that Hispanic women live in locations (e.g., cities) with higher costs of living than whites. After we account for cost of living, the estimated Hispanic-white wage differential for non-immigrant women falls by approximately two-thirds. As a result, we find no statistically significant difference in wages between Hispanic and white women in the NLSY97.
Keywords: J31; J70; R23; 330; Hispanic-white wage disparities; Cost of living differentials; Immigrant and nonimmigrant Hispanics; NLSY